Historical and geographical genetic variation: Europe - Torroni, Antonio (Henry Stewart Talks, 2007)
Origin of modern Europeans, Genetic tools, Neanderthal vs. modern humans, Complete mitochondrial DNA sequences: new data on the early events after the Out of Africa exit, Paleolithic vs. Neolithic origin of the European gene pool, Expansions from glacial refugia after the Last Glacial Maximum, Unexpected genetic links between modern populations: the case of the Saami and Berbers, Population studies at the microgeographic level: the paradigmatic case of the Etruscans
Archived at 2020/08/13